2019
DOI: 10.1097/ccm.0000000000003868
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance in the ICU: A Systematic Review

Abstract: Objectives: To synthesize the literature describing compliance with WHO hand hygiene (HH) guidelines in Intensive Care Units (ICUs), to evaluate the quality of extant research, and to examine differences in compliance rates across geographical regions, ICU types, and healthcare worker groups, observation methods, and Moments (indications) of HH. Data sources: Electronic searches were conducted in August 2018 using Medline, CINAHL, PsycInfo, Embase, and Web of Science. Reference lists of included studies and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
78
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 33 publications
14
78
1
7
Order By: Relevance
“…Despite the high reported use of practices to prevent C difficile infection and CLABSI, actual compliance with many practices (eg, hand washing) was likely lower. 15 Although increases over time were observed for most CAUTI prevention practices, the proportion of hospitals reporting regular use of CAUTI prevention practices was lower compared with the reported use of other HAI prevention practices. This lag may be associated with the relative lack of importance placed on CAUTI by hospital leadership.…”
Section: Discussionmentioning
confidence: 88%
“…Despite the high reported use of practices to prevent C difficile infection and CLABSI, actual compliance with many practices (eg, hand washing) was likely lower. 15 Although increases over time were observed for most CAUTI prevention practices, the proportion of hospitals reporting regular use of CAUTI prevention practices was lower compared with the reported use of other HAI prevention practices. This lag may be associated with the relative lack of importance placed on CAUTI by hospital leadership.…”
Section: Discussionmentioning
confidence: 88%
“…Although effective infection prevention and control (IPC) programmes in health care facilities should meet WHO minimum requirements [1], the 2020 global WASH report revealed that one in three facilities do not have adequate hand hygiene stations at the point of care [2]. A recent systematic review showed that hand hygiene compliance is only around 9% during care of critically ill patients in lowincome countries [3]; such shocking data, in conjunction with the ongoing COVID-19 pandemic, highlight the urgent need for additional efforts to strengthen global compliance and champion best practices. Although vaccines are starting to be delivered, hand hygiene and appropriate use of personal protective equipment remain crucial for safe care of both COVID-19 and non-COVID-19 patients.…”
Section: Open Accessmentioning
confidence: 99%
“…Ennek ellenére a betegek ellátását végző dolgozók kézhigiénés együttműködési készsége alacsony, 50% alatti, melynek oka leggyakrabban a prevenciós ismeretek, az intézményi elkötelezettség és a vezetői példamutatás hiánya (17)(18)(19)(20). Figyelembe véve a fentebb leírtakat, indokolt, hogy a kézhigiénés tevékenységeket az egészségügyi és a szociális intézmények dolgozói is ismerjék és alkalmazzák a krónikus bőrsebek ellátása során is.…”
Section: Kézhigiénéunclassified